Building an Entrepreneurial Society: 25 Years of Entrepreneurship at FEB UM - Rebernik, Miroslav; Bradač Hojnik, Barbara; Crnogaj, Katja; Knez-Riedel, Jožica; Krošlin, Tadej; Močnik, Dijana; Mulej, Matjaž; Pušnik, Ksenja; Rus, Matej; Tominc, Polona (University of Maribor Press, 2018)
The present scientific monograph was formed on the occasion of the anniversary celebrated in the academic year 2017/2018 by current and former members of the Department of Entrepreneurship and Business Economics, and the members of the Institute of Entrepreneurship and Small Business Management at the University of Maribor. Twenty-five years – a quarter of a century – is a period after which it is worth looking back on the past and summing up the memories of the achievements and milestones that have marked it. The monograph is also an acknowledgment and tribute to the initiator and founder of the first study track for entrepreneurship education, and the head of the Department and Institute, Professor Doctor Miroslav Rebernik. The collection of selected scientific contributions is thus put together in such a way that he is the co-author of all of them, with individual members of the Department. A collection was created that chronologically presents some of the most visible contributions of the 25-year period. We would like to thank all publishing houses that approved the reprint of the contributions.